2005
DOI: 10.1111/j.1525-1594.2005.29068.x
|View full text |Cite
|
Sign up to set email alerts
|

On‐line Hemodiafiltration Does Not Induce Inflammatory Response in End‐stage Renal Disease Patients: Results From a Multicenter Cross‐over Study

Abstract: On-line HDF, as the most effective renal replacement therapy, does not provoke inflammatory response and is both safe and highly biocompatible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
2
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 35 publications
1
25
2
2
Order By: Relevance
“…One of the nutritional aspects in dialysis patients is loss of albumin, which depends on the permeability of the membrane used, and increases with increasing ultrafiltrate rates and transmembrane pressures. Some earlier studies either showed no change or even an improvement of albumin levels [30,33,35,37,38]. In the CONTRAST study, a decrease in albumin levels by 1.4% was seen after 6 months of treatment with HDF, while the levels remained stable in the HD group [36].…”
Section: Hdf and Hard Clinical End Pointsmentioning
confidence: 97%
See 2 more Smart Citations
“…One of the nutritional aspects in dialysis patients is loss of albumin, which depends on the permeability of the membrane used, and increases with increasing ultrafiltrate rates and transmembrane pressures. Some earlier studies either showed no change or even an improvement of albumin levels [30,33,35,37,38]. In the CONTRAST study, a decrease in albumin levels by 1.4% was seen after 6 months of treatment with HDF, while the levels remained stable in the HD group [36].…”
Section: Hdf and Hard Clinical End Pointsmentioning
confidence: 97%
“…Although this has indeed been shown for TNF and IL-1, no effect of HDF on the clearance of IL-6R has been demonstrated thus far [25,26,28,30]. HDF with regeneration of ultrafiltrate has been reported to have a positive impact on inflammation and oxidative stress as well.…”
Section: Effects Of Hdf On Uremic Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that RKF or urine volume was more preserved among patients treated with on-line HDF than among those treated with conventional hemodialysis [78, 79]. These observations may be attributed to fewer intradialytic hypotensive episodes and reduced dialyzer-induced systemic inflammation [80]. …”
Section: How To Protect Rkfmentioning
confidence: 97%
“…Apart from other forms of HDF (acetate-free biofi ltration, push-pull, mid-dilution, paired fi ltration dialysis), online HDF has constantly increased its popularity, possibly based on the following facts. Firstly, the unlimited amount of fl uid which can be produced online under proven and experience-based safety protocols will further encourage the application of increased convection [57] . New perspectives in the use of pre-and postinfusion, controlled by the transmembrane pressure ultrafi ltration feedback, may enable a more complete exploitation of the convective mechanism [58] .…”
Section: From Expensive Technical Gadgets To Useful Tools For Routinementioning
confidence: 99%